Student workbook for argument-driven inquiry in fourth-grade science : three-dimensional investigations - Sampson, Victor, 1974-; Murphy, Ashley, 1988- (Arlington, Virginia : National Science Teachers Association, 2019)
This book provides teachers with student materials for guiding students through argument-driven inquiry investigations. It provides lab details, safety information, and handouts that integrate science, literacy, and math.
Section 1. Introduction and investigation safety -- section 2. Energy -- section 3. Waves and their application in technologies for information transfer -- section 4. From molecules to organisms : structures and processes -- section 5. Earth's place in the universe and systems.
eBooks on EBSCOhost
Keywords: Science -- Study and teaching (Elementary) -- Activity programs; Science -- Study and teaching -- Activity programs; Fourth grade (Education); Sciences -- Étude et enseignement (Primaire) -- Méthodes actives; Sciences -- Étude et enseignement -- Méthodes actives; Quatrième année (Éducation); Fourth grade (Education); Science -- Study and teaching -- Activity programs; Science -- Study and teaching (Elementary) -- Activity programs